Zasnova prototipa informacijskega sistema za klinično pot otročnice in novorojenca v zgodnjem poporodnem in neonatalnem obdobju - Višić, Uroš (Obzornik zdravstvene nege, 2021)
Introduction: Clinical pathway is a methodology that enables all members of a healthcare team to practise rational and well-considered treatment that is based on good practice, as well as monitoring of the work and simplified documentation. The aim of this study was to identify the clinical pathway for an effective treatment of mothers in neonatal period and develop a prototype of the information system that would facilitate the implementation of this path. Methods: A literature review identified an existing clinical pathway. A prototype of the information system was designed using a modeling method and structured interviews with 6 focus group participants. The prototype was evaluated by identifying patterns and key topics from the clinical settings. Results: Judgement criteria of focus group participants for prototype evaluation indicate that the information system prototype can adequately support the presented clinical pathway. Improvements made by focus group participants were subsequently incorporated into the developed prototype. Discussion and conclusion: Nurses represent an important connection in treatments within the clinical pathway system in the early postnatal period. By introducing treatment of the clinical pathway system, which is supported by the proposed information system, the method of documenting treatments in the implementation of the clinical pathway can be significantly improved. By reducing unnecessary double recording, nurses would gain time and use it more efficiently.
Keywords: documentation; dokumentiranje; health education; kakovost; nursing; obravnava; quality; treatment; zdravstvena nega; zdravstvena vzgoja